2011
DOI: 10.1002/jtr.835
|View full text |Cite
|
Sign up to set email alerts
|

Shopping orientation and online travel shopping: The role of travel experience

Abstract: This paper investigates how consumers'shopping orientation toward travel shopping infl uences their tendency to shop for travel products on the Internet. The paper also looks into the role of consumers' travel experience. A conceptual model is developed and a number of hypotheses are forwarded and tested by structural equation modeling, using data from 256 respondents. The results support several of the stated hypotheses. Shopping orientation and travel experience both infl uence travelers' intentions to shop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 45 publications
3
65
0
3
Order By: Relevance
“…For example, travelers that are time-saving oriented tend to value convenience that was found to influence intentions to purchase travel online. In a later study, using price-saving orientation, time-saving orientation, information orientation, personalized orientation, and store-enjoyment orientation, Jensen (2012) found that the only shopping orientation that had a direct effect on online travel purchasing was store-enjoyment orientation. Indeed, the results revealed that storeenjoyment oriented consumers were less likely to purchase travel products online.…”
Section: Consumer Shopping Orientationsmentioning
confidence: 94%
See 4 more Smart Citations
“…For example, travelers that are time-saving oriented tend to value convenience that was found to influence intentions to purchase travel online. In a later study, using price-saving orientation, time-saving orientation, information orientation, personalized orientation, and store-enjoyment orientation, Jensen (2012) found that the only shopping orientation that had a direct effect on online travel purchasing was store-enjoyment orientation. Indeed, the results revealed that storeenjoyment oriented consumers were less likely to purchase travel products online.…”
Section: Consumer Shopping Orientationsmentioning
confidence: 94%
“…For instance, several studies have found that travelers that search for travel information online are more likely to purchase travel online (Jensen, 2012;Kamarulzaman, 2007Kamarulzaman, , 2010Susskind & Stefanone, 2010;Wen, 2010;Wolfe et al, 2004). Despite this being an expectable finding, Jensen (2012) found that this relationship was weak, reflecting that online travel search may not necessarily be followed by an online travel purchase.…”
Section: Travel-related Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations